If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7 = 3x + -11 Reorder the terms: -7 + 6x = 3x + -11 Reorder the terms: -7 + 6x = -11 + 3x Solving -7 + 6x = -11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + 6x + -3x = -11 + 3x + -3x Combine like terms: 6x + -3x = 3x -7 + 3x = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 -7 + 3x = -11 + 0 -7 + 3x = -11 Add '7' to each side of the equation. -7 + 7 + 3x = -11 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = -11 + 7 3x = -11 + 7 Combine like terms: -11 + 7 = -4 3x = -4 Divide each side by '3'. x = -1.333333333 Simplifying x = -1.333333333
| 9(2x+14)-4(3x+17)=64 | | -3x+6=18 | | 3x^2-27x=-2x^2-9x-16 | | 5.50+4.00(486-a)=2416 | | -486=6(7x-11) | | 7-8x=47-22x | | 3x-5=5x+12 | | 4(5y-4)=12y | | -61*3=x | | -120=-4(7x+9) | | 5y-9=7y-13 | | 4x+6=4x+6 | | 3x=5+2(3+4) | | 2x+3x=2x+40 | | 3x+(x-8)=12 | | 7y=6(y+10) | | x+x+2+3x=57 | | [x-5]=-9 | | -(4y+3z-2)= | | [x-5]=9 | | 96=-3(-5x-7) | | 6--7=3x+8-2x | | -2+11=15x-4-14x | | x+3(x-4)=-72 | | (x+10)*(x+10)=9 | | -8-2x=-7-7x | | -4-6=12-10x | | -99=-3(-7x-2) | | 6x+4x=200 | | -6.5+x=12.25 | | 6g-6-3-6g= | | -3y-12=5y+44 |